Phenylalanine and Tryptophan Intake of Hyperactive Children with Autism - Puspito Arum; Dahlia Indah Amareta; Faridlotul Zannah (Journal of Biomedicine and Translational Research, 2017)
Background: Hyperactive is behavior which demonstrates the attitude of more energy than normal behavior. Level of neurotransmitter dopamine and serotonin in the body may be the factor of this disorder behavior.  Level of phenylalanine and serotonin were found high in hyperactive children with autism. Level phenylalanine in the brain shows that it is not changed into tyrosine so dopamine can not be form. Serotonin derived from an amino acid tryptophan.Objective: To understand the association between phenylalanine and tryptophan intake to hyperactivity of  children with autism.Methods: A survey analytic research with cross sectional approach involving 20 subjects. Phenylalanine and tryptophan intake data was collected by Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ), and hyperactivity disorder of children with autism was measured based on DSM-IV guidelines. Results: Eight (40%) children had low hyperactivity, 9 (45%) children had moderate hyperactivity, 2 (10%) children had severe hyperactivity, and 1 (5%) child had very severe hyperactivity. Mean phenylalanine intake was 4899.74mg (±1543.42) with maximum and minimum intake respectively 7735.42mg and 1843.88mg. Tryptophan intake was 1153.91mg (±384.99) with maximum and minimum intake respectively 1953.89mg and 367.69mg. There was significant association between phenylalanine intake (p=0,034; r=0,477) and tryptophan intake and hyperactivity (p=0,026; r=0,492).Conclusion: There is an association between intakes of amino acid phenylalanine and amino acid tryptophan with hyperactivity of autistic children